2022
DOI: 10.1016/j.spinee.2022.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle and soluble fractions of adipose tissue-derived mesenchymal stem cells secretome induce inflammatory cytokines modulation in an in vitro model of discogenic pain

Abstract: árez , Extracellular vesicle and soluble fractions of adipose tissue-derived mesenchymal stem cells secretome induce inflammatory cytokines modulation in an in vitro model of discogenic pain,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
(70 reference statements)
3
8
0
Order By: Relevance
“…The data in this study adds to the current literature supported by others [47] and positions the signi cant advantages of using the whole secretome compared with the EV populations in key aspects of the MSC regenerative spectrum thanks to its increased immunomodulation abilities and superior angiogenic properties.…”
Section: Discussionsupporting
confidence: 67%
“…The data in this study adds to the current literature supported by others [47] and positions the signi cant advantages of using the whole secretome compared with the EV populations in key aspects of the MSC regenerative spectrum thanks to its increased immunomodulation abilities and superior angiogenic properties.…”
Section: Discussionsupporting
confidence: 67%
“…González-Cubero et al. showed that EVs and soluble fractions from conditioned media promote an in vitro anti-inflammatory modulation in intervertebral disc degeneration in a “highly synergistic way”, thus highlighting that the use of the whole secretome rather than isolated EVs might be more beneficial for therapy ( 21 ). While it is still hard to understand what exactly mediates the immunomodulatory potential, the effect might come from a synergistic combination of both the soluble factors from the secretome and the EVs.…”
Section: Multiparametric Influence On the Immunomodulatory Potential ...mentioning
confidence: 99%
“…It is hypothesized that obesity, especially abdominal obesity, exerts additional mechanical stress on the lower back, resulting in pain ( 59 ). In addition, adipose tissue can secrete pro-inflammatory cytokines, which could contribute to LBP ( 60 , 61 ). Accordingly, weight management may still offer benefits for LBP prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%